Analysis of Constraints, Perceptions, and Determining Factors for Success in Implementing the Merdeka Belajar Curriculum in Indonesia: A Case Study at Muhammadiyah Kasihan Bantul Middle School, Special Region of Yogyakarta - Trisna Sukmayadi; Sumaryati; Ali Tarmuji (The Indonesian Institute of Science and Technology Research, 2026)
This research aims to analyze the obstacles, perceptions, and success factors in implementing the Merdeka Belajar Curriculum at Muhammadiyah Kasihan Middle School. The method is a descriptive qualitative approach, utilizing in-depth interviews with Pancasila and Civic Education (Pendidikan Pancasial dan Kewarganegaraan or PPKn) teachers at various levels. The results showed that the main obstacles lie in understanding the new curriculum, limited references, and a lack of relevant training. Nevertheless, teachers' perceptions of curriculum change tend to be positive when supported by adequate training and sufficient resources. The implications of this study demonstrate the importance of strengthening teacher capacity as well as providing systematic support to make curriculum implementation work more effectively.